2008
DOI: 10.1007/s00299-008-0621-y
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Coffea canephora and C. arabica karyotype based on chromosomal DNA content

Abstract: Nuclear genome size has been measured in various plants, seeing that knowledge of the DNA content is useful for taxonomic and evolutive studies, plant breeding programs and genome sequencing projects. Besides the nuclear DNA content, tools and protocols to quantify the chromosomal DNA content have been also applied, expanding the data about genomic structure. This study was conducted in order to calculate the Coffea canephora and Coffea arabica chromosomal DNA content, associating cytogenetic methodologies wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 44 publications
1
22
1
Order By: Relevance
“…Garner (2002) observed that the percentage of SSR primers that do not produce PCR products is high and positively correlated to the size of the genomes. We found, however, that the conversion rate in C. arabica (93.7%) was higher than in C. canephora (75.8%, Hendre et al 2008), nevertheless the double of the size of C. arabica genome, respectively, 2,56x10 9 bp and 1,38x10 9 bp (Clarindo and Carvalho 2009). Conversion rates similar of C. arabica were reported for Corchorus capsularis (91.0%, Mir et al 2008), Lolium multiflorum (90.4%, Hirata et al 2006), Cucurbitaceas (94.0%, Gong et al 2008), Humulus lupulus (92.2%, Stajner et al 2005), and Avena sativa (95.5%, Li et al 2000).…”
Section: Validation Of the Ssr Markers For C Arabicacontrasting
confidence: 41%
“…Garner (2002) observed that the percentage of SSR primers that do not produce PCR products is high and positively correlated to the size of the genomes. We found, however, that the conversion rate in C. arabica (93.7%) was higher than in C. canephora (75.8%, Hendre et al 2008), nevertheless the double of the size of C. arabica genome, respectively, 2,56x10 9 bp and 1,38x10 9 bp (Clarindo and Carvalho 2009). Conversion rates similar of C. arabica were reported for Corchorus capsularis (91.0%, Mir et al 2008), Lolium multiflorum (90.4%, Hirata et al 2006), Cucurbitaceas (94.0%, Gong et al 2008), Humulus lupulus (92.2%, Stajner et al 2005), and Avena sativa (95.5%, Li et al 2000).…”
Section: Validation Of the Ssr Markers For C Arabicacontrasting
confidence: 41%
“…Subsequently, 0.5 mL of the same buffer was added and the homogenate was filtered in a 30 μm nylon filter (Partec ® ) into a 2.0 microcentrifuge tube (Eppendorf ® ), and then centrifuged at 100 g for 5 min. The supernatant was poured out and the pellet was resuspended and incubated for 10 min in a 100 μL OTTO I lysis buffer [13].…”
Section: Methodsmentioning
confidence: 99%
“…arabica originated from a cross between two diploid species of the genus Coffea with similar genomes (Raina et al 1998;Yu et al 2011). Some diploid species have been especially pointed out as possible progenitors of this species, for instance, C. canephora (Lashermes et al 1997;Clarindo and Carvalho 2009;Yu et al 2011), and C. congensis (Lashermes et al 1997;Raina et al 1998). However, more recent evolutive data, obtained by Hamon et al (2009) from 16 species of Coffea, support the view of Raina et al (1998) that C. arabica is a hybrid of Coffea eugenioides and C. congensis.…”
Section: Cytogenetic Analysismentioning
confidence: 99%
“…A. Froehner Carvalho 2006, 2009) and C. arabica Carvalho 2008, 2009), and accurate karyograms were assembled for these species. Karyomorphological features indicated that C. arabica is a true allotetraploid species Carvalho 2008, 2009), and C. canephora may be one of its diploid progenitors (Clarindo and Carvalho 2009). Despite these improvements, assembling the karyotype of other Coffea species is important to accomplish evolutive studies and identify the progenitor species of C. arabica, which is a matter of general interest (Clarindo and Carvalho 2009).…”
Section: Introductionmentioning
confidence: 98%